2021
DOI: 10.1002/dvdy.312
|View full text |Cite
|
Sign up to set email alerts
|

Genetic disruption of zebrafish mab21l1 reveals a conserved role in eye development and affected pathways

Abstract: Background The male‐abnormal 21 like (MAB21L) genes are important in human ocular development. Homozygous loss of MAB21L1 leads to corneal dystrophy in all affected individuals along with cataracts and buphthalmos in some. The molecular function and downstream pathways of MAB21L factors are largely undefined. Results We generated the first mab21l1 zebrafish mutant carrying a putative loss‐of‐function allele, c.107delA p.(Lys36Argfs*7). At the final stages of embryonic development, homozygous mab21l1c.107delA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 91 publications
(149 reference statements)
0
15
0
Order By: Relevance
“…To further study the cornea defects, 30-dpf foxc1a ∆CED1−3 mutant sections were stained for N-cadherin (cdh2) that marks corneal epithelium and endothelium, and corneal keratan sulfate proteoglycan (CKS), which is a marker for corneal stroma [ 31 ]. Cornea epithelium at 30-dpf is composed of several layers of epithelial cells, an acellular and well-ordered stroma, and an endothelial monolayer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further study the cornea defects, 30-dpf foxc1a ∆CED1−3 mutant sections were stained for N-cadherin (cdh2) that marks corneal epithelium and endothelium, and corneal keratan sulfate proteoglycan (CKS), which is a marker for corneal stroma [ 31 ]. Cornea epithelium at 30-dpf is composed of several layers of epithelial cells, an acellular and well-ordered stroma, and an endothelial monolayer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in human Mab21L1 gene causes aberrations in lens ectoderm morphogenesis and lead to congenital cerebellar, ocular, craniofacial and genital (COFG) syndrome [ 101 , 102 ]. The ocular abnormalities include microphthalmia, coloboma and cataracts [ 7 , 9 ]. Similar to human mab21L1 gene mutations, Mab21L1-deficient mice display severe cell-autonomous defects in lens placode invagination due to impaired cell proliferation and survival [ 5 ] and other deficiency [ 6 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later it was found that Mab21L1 is a lens lineage-specific transcription factor [100]. It has an important role in regulating lens development [5,[7][8][9]11]. Mutations in human Mab21L1 gene causes aberrations in lens ectoderm morphogenesis and lead to congenital cerebellar, ocular, craniofacial and genital (COFG) syndrome [101,102].…”
Section: Mab21l1 Positively Regulates αB-crystallin To Promote Surviv...mentioning
confidence: 99%
See 2 more Smart Citations